1976
DOI: 10.1152/ajplegacy.1976.231.5.1466
|View full text |Cite
|
Sign up to set email alerts
|

Protein composition of lung fluids in anesthetized dogs with acute cardiogenic edema

Abstract: We measured the protein composition of plasma and lung fluids from nine dogs with cardiogenic edema. To produce the edema, we increased left atrial pressure an average of 36 cmH2O by inflating a balloon catheter in the left atrium, infusing norepinephrine, and infusing large volumes of saline or saline-diluted blood. Blood samples were collected every 15 min, and airway fluid was collected from five dogs that developed severe edema. Terminally, the chest was opened and the lungs were removed. Samples of alveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
4

Year Published

1978
1978
1988
1988

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 0 publications
1
13
0
4
Order By: Relevance
“…Previous studies (18) have shown that it is difficult to produce alveolar flooding in dogs by simply raising the pulmonary vascular pressures. Vreim et al (3) showed that in high pressure pulmonary edema, with the extravascular lung water-to-dry weight ratio ranging from 6.6 to 15.7, the alveolar flooding was less obvious. However, they had much less difficulty producing alveolar flooding in low pressure pulmonary edema (2).…”
Section: Fitc Tracer Studiesmentioning
confidence: 99%
“…Previous studies (18) have shown that it is difficult to produce alveolar flooding in dogs by simply raising the pulmonary vascular pressures. Vreim et al (3) showed that in high pressure pulmonary edema, with the extravascular lung water-to-dry weight ratio ranging from 6.6 to 15.7, the alveolar flooding was less obvious. However, they had much less difficulty producing alveolar flooding in low pressure pulmonary edema (2).…”
Section: Fitc Tracer Studiesmentioning
confidence: 99%
“…Lymph collected this way is largely from the lungs (8,9). Also, lymph protein concentration appears to reflect protein concentration in the lung perimicrovascular space (10,11). Under steady-state conditions, we assume that lymph flow is proportional to the net volume of fluid filtered from lung exchanging vessels.…”
Section: Description Of Sheep Preparationmentioning
confidence: 99%
“…Animal studies in which alveolar fluid was obtained by direct alveolar micropuncture have shown that the protein concentration of alveolar fluid is similar to that of fluid in the airways in both cardiac and permeability types of pulmonary edema [19,20]. Clinical studies have shown that the analysis of edema protein relative to plasma protein concentrations is useful in separating these two types of pulmonary edema.…”
Section: Discussionmentioning
confidence: 99%